Adulthood Animal Abuse Among Men Arrested for Domestic Violence. (September 2014) - Febres, Jeniimarie; Brasfield, Hope; Shorey, Ryan C.; Elmquist, Joanna; Ninnemann, Andrew; Schonbrun, Yael C.; Temple, Jeff R.; Recupero, Patricia R.; Stuart, Gregory L.
Learning more about intimate partner violence (IPV), perpetrators could aid the development of more effective treatments. The prevalence of adulthood animal abuse (AAA) perpetration and its association with IPV perpetration, antisociality, and alcohol use in 307 men arrested for domestic violence were examined. Forty-one percent ( n = 125) of the men committed at least one act of animal abuse since the age of 18, in contrast to the 1.5% prevalence rate reported by men in the general population. Controlling for antisociality and alcohol use, AAA showed a trend toward a significant association with physical and severe psychological IPV perpetration.